Randomized Load-balancing for Parallel Branch-and-bound Algorithms for Multi-level Network Design - Cruz, F. R. B.; Mateus, G. R.; Smith, J. MacGregor (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2000)
This paper is concerned with parallel implementations of the classical branch-and-bound algorithm for a multi-level network optimization problem. Multi-level network optimization problems arise in many contexts such as telecommunication, transportation, or electric power systems. A new model for multi-level network design is introduced and formulated as a mixed-integer program. The formulation is innovative because it integrates in the same model aspects of discrete facility location topological network design, and dimensioning. We propose implementations which are suitable for MIMD (multiple instruction stream, multiple data stream) parallel computation systems. Thus, the implementations are very convenient for use in networks of workstations which nowadays has become so popular. We have tested two versions of the branch-and-bound algorithm as well as different load balancing strategies. The results are very encouraging indicating a gain over sequential computations in terms of execution time.